<span>Simplifying
6(x + -1) = 9(x + 2)
Reorder the terms:
6(-1 + x) = 9(x + 2)
(-1 * 6 + x * 6) = 9(x + 2)
(-6 + 6x) = 9(x + 2)
Reorder the terms:
-6 + 6x = 9(2 + x)
-6 + 6x = (2 * 9 + x * 9)
-6 + 6x = (18 + 9x)
Solving
-6 + 6x = 18 + 9x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-9x' to each side of the equation.
-6 + 6x + -9x = 18 + 9x + -9x
Combine like terms: 6x + -9x = -3x
-6 + -3x = 18 + 9x + -9x
Combine like terms: 9x + -9x = 0
-6 + -3x = 18 + 0
-6 + -3x = 18
Add '6' to each side of the equation.
-6 + 6 + -3x = 18 + 6
Combine like terms: -6 + 6 = 0
0 + -3x = 18 + 6
-3x = 18 + 6
Combine like terms: 18 + 6 = 24
-3x = 24
Divide each side by '-3'.
x = -8
Simplifying
x = -8</span>
Answer:
1 1/4
Step-by-step explanation:
Answer:
42.5
Step-by-step explanation:
Multiply 50 by 0.85, which equals 42.5.
Answer:
9r
Step-by-step explanation:
combine like terms in PEMDAS order. Add 4, 9, and 7, then, subtract 11.
Answer:
The ratio would be, 4 tablespoons of honey: 5 cups of flour
Step-by-step explanation:
4/5 is the simplified version of 8/10, which is what we were first given